Tumor Biology and Microenvironment of Vestibular Schwannoma-Relation to Tumor Growth and Hearing Loss - Tesařová, Michaela; Peterková, Lenka; Šťastná, Monika; Kolář, Michal; Lacina, Lukáš; Smetana, Karel; Hynek, Radovan; Betka, Jan; Vlasák, Aleš; Lukeš, Petr; Fík, Zdeněk (Biomedicines, 2022)
Vestibular schwannoma is the most common benign neoplasm of the cerebellopontine angle. It arises from Schwann cells of the vestibular nerve. The first symptoms of vestibular schwannoma include hearing loss, tinnitus, and vestibular symptoms. In the event of further growth, cerebellar and brainstem symptoms, along with palsy of the adjacent cranial nerves, may be present. Although hearing impairment is present in 95% of patients diagnosed with vestibular schwannoma, most tumors do not progress in size or have low growth rates. However, the clinical picture has unpredictable dynamics, and there are currently no reliable predictors of the tumor's behavior. The etiology of the hearing loss in patients with vestibular schwannoma is unclear. Given the presence of hearing loss in patients with non-growing tumors, a purely mechanistic approach is insufficient. A possible explanation for this may be that the function of the auditory system may be affected by the paracrine activity of the tumor. Moreover, initiation of the development and growth progression of vestibular schwannomas is not yet clearly understood. Biallelic loss of the NF2 gene does not explain the occurrence in all patients; therefore, detection of gene expression abnormalities in cases of progressive growth is required. As in other areas of cancer research, the tumor microenvironment is coming to the forefront, also in vestibular schwannomas. In the paradigm of the tumor microenvironment, the stroma of the tumor actively influences the tumor's behavior. However, research in the area of vestibular schwannomas is at an early stage. Thus, knowledge of the molecular mechanisms of tumorigenesis and interactions between cells present within the tumor is crucial for the diagnosis, prediction of tumor behavior, and targeted therapeutic interventions. In this review, we provide an overview of the current knowledge in the field of molecular biology and tumor microenvironment of vestibular schwannomas, as well as their relationship to tumor growth and hearing loss.